Pengembangan Profesionalisme Guru Dalam Mewujudkan Kualitas Pendidikan Di Indonesia - Hani Risdiany (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2021)
Government efforts to develop the teaching profession as a strong and respected profession on a par with other professions seen from the birth of Law No. 14 of 2005 on Teachers and Lecturers who do business the teaching profession develops legal protection. The government has made efforts to improve teacher professionalism increase qualifications and education level requirements higher level for teaching staff from the school level to College. Another effort made by the government is a program Certification and Notification of PKG (Teacher Activity Center, MGMP (Subject Teacher Deliberation), and KKG (Teacher Working Group). Professional teachers must have 4 competencies, namely: pedagogical competence, personal competence, social competence, and professional competence, as well as what is important and needs to be done by the government is building independence among teachers. This independence will grow professional and innovative attitude towards teachers in carrying out their roles and his job is to educate people towards a better life and quality.